Height of jump and maximal power output of the lower limbs in volleyball players - Buśko, Krzysztof; Szulc, Adam Michał; Kamiński, Marek (Journal of Education, Health and Sport, 2015)
Buśko Krzysztof, Szulc Adam, Kamiński Marek. Height of jump and maximal power output of the lower limbs in volleyball players. Journal of Education, Health and Sport. 2015;5(9):747-753. ISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44237 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A747-753 https://pbn.nauka.gov.pl/works/687072 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014: http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 31.10.2015. Height of jump and maximal power output of the lower limbs in volleyball players Buśko Krzysztof1, Adam Szulc2, Marek Kamiński2 1 – Zakład Biomechaniki, Instytut Sportu – Państwowy Instytut Badawczy, Warszawa 2 – Instytut Kultury Fizycznej, Uniwersytet Kazimierza Wielkiego, Bydgoszcz 1 – Department of Biomechanics, Institute of Sport – National Research Institute, Warsaw, Poland 2 – Institute of Physical Culture, Kazimierz Wielki University, Bydgoszcz, Poland Buśko Krzysztof, dr hab. prof. nadzw. Zakład Biomechaniki, Instytut Sportu – Państwowy Instytut Badawczy, Trylogii 2/16, 01-982 Warszawa Tel. 22 8340812 w. 247 krzysztof.busko@insp.waw.pl Abstract The aim of the study was to compare the results obtained in the coaching tests (block jump and spike jump) with the results of laboratory tests (counter-movement jump and spike jump performed on force plate) in volleyball players. The study involved 16 volleyball players. Characteristics of participants: age 17.2 ± 0.7 years, body height 196.2 ± 7.6 cm, body mass 86.4 ± 10.0 kg, training experience of 7.8 ± 1.6 years. Each volleyball player performed coaching test consisting of three block jumps and three spike jumps, and laboratory test consisting of three counter-movement jump (CMJ) and three spike jump (SPJ) performed on force plate. The mean values obtained by the competitors in the coaching test were: height in block jump 47.6±5.2 cm, height in spike jump 72.4±7.6 cm, and laboratory test: the height of rise of the body’s centre of mass in the CMJ 47.9±4.0 cm and SPJ 60.8 ±5.7 cm. Significant differences were found between height in spike jump and the height of rise of the body’s centre of mass in the SPJ. Significant relationship were found between the height of jump obtained during laboratory and coaching tests. In conclusion, height of jump in CMJ measured in coaching test doesn’t differ from the height of rise of the body’s centre of mass measured in SPJ jump on force plate (laboratory tests).